Possible restrictions of mathematics learning in transition from a teaching model to a learning model - Novikienė, Regina; Petraitienė, Stasė (Lietuvos matematikos rinkinys, 2002)
The problem on changes of higher education pedagogics, however, is particularly urgent, since traditional pedagogics, when teaching is considered as a communication process meets demands of society no longer. A traditional education form, i.e., a lecture, does not develop abilities, possession of which would lead to the formation of a studying society. Thus a problem occurs, which may be defined by the following questions: ln which way a didactic process shall be organised in order to ensure the development of necessary abilities? What are the restrictions, characteristic to the transition to the process mentioned? The article consists of two parts. First part discusses the way for theoretical grounding of a change possibility for a mathematics learning model. Second part reveals theoretic restrictions, which may occur, while changing a model of studying.